THE EFFECT OF THE ECONOMIC GLOBALIZATION ON THE ECONOMIC GROWTH IN BULGARIA (Revista Inclusiones, 2021)
The paper examines the impact of the economic globalization on the economic growth in Bulgaria for the period 2007-2018. The aim of the tudy is to reveal the impact of the economic globalization on the economic growth. The research of the link economic globalization and its influence on the economic growth is performed via generalized method of moments (GMM), descriptive analysis and deductive approach. The conclusion that has been reached is that economic globalization has a positive impact on the economic growth for the period 2007-2018. The main channel of influence is the international trade.